Joint Preservation of the Wrist Using Articulated Distraction Arthroplasty: A Case Report of a Novel Technique - Matt D. A. Fletcher (Case Reports in Orthopedics)
Distraction arthroplasty of the ankle, elbow, and hip has become widely accepted and used within the orthopaedic community with excellent initial results which appear sustained. To date it has not been applied to the wrist in the same manner. A novel technique, drawn upon past success of articulated ankle distraction and static wrist distraction, was devised and evaluated by application of articulated wrist distraction performed over a 12-week period in a patient with poor functional outcome following limited wrist fusion. Posttreatment results showed improvement in range of motion (100-degree arc), subjective pain, and functional outcome measures (DASH 21.7, Mayo Wrist Score 80) comparable or better than either limited wrist fusion or proximal row carpectomy. Articulated wrist distraction initially appears to be a promising therapeutic option for the management of the stiff and painful wrist to maintain maximal function for which formal wrist arthrodesis may be the only alternative.